Peran Lembaga Arbitrase Syariah Dalam Mendukung Keamanan Investasi di Dunia Bisnis Islam - Dede Khoirunnisa; Wagianto Wagianto; Asriani Asriani (Media of Law and Sharia, 2024)
In the era of globalization and growing business dynamics, Islamic business has become an integral part of the global economy. Along with this growth, the role of Sharia Arbitration Institutions has emerged as a key element in maintaining investment stability and security in the Islamic business world. The Sharia Arbitration Institute is an institution that plays a role in resolving sharia disputes peacefully outside the general court. The aim of this research is to analyze the role of Sharia Arbitration Institutions in supporting investment security in the Islamic business world. This research is normative legal research using a statutory approach. The research results show that the role of Sharia Arbitration Institutions in increasing the security of business investments is realized through a strong legal basis involving laws, fatwas, decrees, regulations of certain legal institutions that regulate the operations of these institutions. So this can encourage more investors to get involved in Islamic business, because they know that if a dispute occurs, the resolution will be carried out in accordance with sharia principles Kata Kunci: Lembaga Arbitrase Syariah, Keamanan Investasi, dan Perinsip Syariah   Abstract: The Shariah Arbitration Institution plays a pivotal role in supporting investment security within the realm of Islamic business. In this context, this institution functions as an alternative dispute resolution mechanism grounded in Islamic legal principles. This article delves into the crucial role of Shariah arbitration institutions in safeguarding and facilitating investment security within the Islamic business environment. The discussion involves an analysis of the Shariah principles adopted by arbitration bodies, the dispute resolution process, and its impact on the investment climate. Keywords: Shariah Arbitration Institution, Investment Security, Shariah Principles